Transformation of Academic Supervision Through Reflective Coaching: Development of Clinical Supervision Models to Improve the Learning Performance of Junior High School Teachers - Tesi Eka Putri; Rusdinal; Rifma; Merika Setiawati (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
Improving teachers’ instructional performance requires supervision practices that do more than assess administrative compliance. This study aimed to develop a clinical supervision model based on reflective coaching to support the continuous improvement of junior high school teachers’ instructional performance. A Research and Development (R&D) approach was employed using the ADDIE framework, comprising Analysis, Design, Development, Implementation, and Evaluation. The development process began with an analysis of existing supervision practices and teachers’ needs, followed by the design and development of the model and its supporting instruments. The initial product was reviewed by experts in educational supervision, instructional materials, learning, and language and subsequently revised according to their recommendations. The revised model was implemented with junior high school teachers to examine its practicality and applicability in an authentic school setting. The findings indicated that the developed model met the required feasibility aspects and could be implemented through clear supervision procedures, usable supporting instruments, classroom observation, reflective dialogue, and follow-up activities. Its implementation was associated with improvements in lesson planning, classroom instruction, learning evaluation, reflective practice, and the refinement of instructional strategies. The study concludes that integrating reflective coaching into clinical supervision can strengthen the developmental function of academic supervision by positioning teachers as active participants in professional learning. The model provides a practical framework for transforming supervision into a collaborative and reflective process that supports sustained improvement in teaching practice.